The effectiveness of special economic zone incentives as a tool for investment promotion and attraction of foreign direct investment inflows : a case of OR Tambo International Airport (ORTIA) SEZ - Makuya, Tshamaano (My University, 2023)
This study draws attention to various challenges that hindered the OR Tambo International Airport Special Economic Zone’s (SEZ) Investment Marketing and Promotion (IMP) Unit from meeting its set foreign direct investment (FDI) targets. It was noted that since 2017, the SEZ’s FDI inflows were persistently on a negative trajectory, despite several attempts by the IMP unit to improve the situation. The unit was further concerned that despite spending millions of rands ramping up its investment marketing effort, the unfortunate reality was that these campaigns did not deliver the desired impacts. Worse still, it was noted that a number of investment pledges signed-off a decade ago were yet to be effectively activated or operationalised. As a result, management resorted to either temporarily suspending earmarked pipeline projects or effectively abandoning them altogether. Within this context, this study sought to evaluate the effectiveness of the existing IMP strategies employed by the SEZ. In doing so, the study made use of the qualitative research method to give people with intimate knowledge of the issues at stake an opportunity to participate in the study in order to better understand the current situation. By using a purposive sampling method, ten participants drawn from the SEZ’s management structure took part in the study. The study also relied on data obtained from relevant SEZ reports. The study found that the current IMP strategy is due for a review as it was evidently unfit-for-purpose. Furthermore, it was also found that the SEZ’s IMP unit lacks the right mix of required experience, skills, technical capacity and pedigree to drive a results-based IMP operation. The study also found the country’s fragile investment climate exacerbated the SEZ’s FDI activation plight. Various recommendations to remedy the problem are suggested. These include, among other things; the need to rethink and reset the current IMP strategy; the need to retool the IMP unit; the need to forge synergies between the SEZ and South African embassies abroad; and the need to diversify existing FDI markets.
Thesis (MBA.) -- University of Limpopo, 2023
Keywords: Foreign direct investment; Investment marketing and promotion; Special economic zones; Investments, foreign; Investment advisors -- Marketing